Calculating energy and its spatial distribution for a subsurface urban heat island using a GIS-approach - Schweighofer, Julian; Wehrl, Michael; Baumgärtel, Sebastian; Rohn, Joachim (Geosciences, 2021)
In urban areas, the human influence on the city-ecosystem often results in a Subsurface Urban Heat Island (SUHI), which can be used geothermally. Unfortunately, a model of a SUHI does not consider the geology and hydrogeology of the subsoil. These can vary significantly over short distances, and are of considerable importance for the energy balance. In this work, we calculated the energy and its density stored in the subsoil via a SUHI. For this so-called energy-SUHI (e-SUHI), we evaluated the geology and its physical parameters for the first 20 m below ground level in the German city of Nuremberg and linked them to measured underground temperatures in a GIS application. This approach revealed stored energy of 1.634 × 1010 MJ within the soil and water for the study area with an area of 163 km2 and a volume of 3.26 × 109 m3. It corresponds to an average energy density of 5.0 MJ/m3. The highest energy density of 16.5 MJ/m3 was found in the city center area and correlated well to increases in subsurface temperature. As expected, our model reacts sensitively to thickness changes in the geological layers and the unsaturated zone.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Energy-SUHI; Geothermal energy; GIS; Subsurface Urban Heat Island (SUHI)